Brand Awareness, Brand Association, dan Perceived Quality terhadap Loyalitas pada pengguna Shopeefood di FEB Unisma Jurusan Manajemen angkatan 2017. - Salman Ainurridho; Siti Asiyah; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of Brand Awareness, Brand Association, and Perceived Quality on Loyalty to Shopeefood users at FEB Unisma majoring in Management in the class of 2017. The variables used in this study are Brand Awareness, Brand Association, Perceived Quality, and Loyalty variables. Data collected through the questionnaire method with the number of samples used as respondents as many as 60 respondents. The results of this study conclude that there is a significant and simultaneous influence of Brand Awareness, Brand Association, Perceived Quality on Loyalty to Shopeefood users at FEB Unisma majoring in Management Force 2017. Brand Awareness has a significant and partial effect on Loyalty to Shopeefood users at FEB Unisma majoring in Force Management. 2017. Brand Association has a significant and partial effect on Loyalty to Shopeefood users at FEB Unisma majoring in Management Class 2017. Perceived Quality has a significant and Partial effect on Loyalty to Shopeefood users at FEB Unisma majoring in Management Class 2017. Keywords: Brand Awareness, Brand Association, Perceived Quality, Loyalty